Pengaruh Etos Kerja dan Budaya Organisasi terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Intervening (Studi Kasus pada CV. Gia Sentosa Kab. Tangerang) - Maharani, Arista Dwi; Kambara, Roni; Khaerunnisa, Enis (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This research aims to analyze the influence of Work Ethic (X1) and Organizational Culture (X2) on Employee Performance (Y), with Organizational Commitment as an intervening variable at CV. Gia Sentosa, Tangerang Regency. The research method uses a descriptive quantitative approach. The research population involved 77 CV employees. Gia Sentosa, and the entire population was sampled using census sampling techniques. Data analysis was carried out using Structural Equation Modeling (SEM) with the SmartPLS 4.1.0.8 student version tool. The research results show that: (1) Work Ethic has a positive and significant influence on Employee Performance; (2) Organizational culture has a positive and significant effect on employee performance; (3) Work Ethic has a positive and significant effect on Organizational Commitment; (4) Organizational Commitment has a positive and significant effect on Employee Performance; and (5) Organizational Commitment is able to mediate the relationship between Work Ethics and Employee Performance.